Óleo essencial de limão: sua possível aplicação em emulsões pelo método de coacervação complexa com wpc:pec - Ambrosio, Guilherme Domingues (Universidade Federal de São Carlos, 2023)
The accumulation of agro-industrial residues over the past years serves as a trigger in the search for their utilization. That is, besides the reduction of environmental impacts, it enables the development of new technologies and strategies for application in new products. The citrus juice industries produce a large amount of residues, and it is possible to obtain lemon essential oils and pectins from the different fractions of the fruit. The former is potentially applied and used in the cosmetics, food and pharmaceutical industries, since it has favorable chemical and sensory properties in the application for the development of new formulations. Pectin (PEC) has numerous applications, such as gelling agent, and its ability to be used as a natural stabilizer is the object of study, besides having the potential to interact with proteins. Aligned with this context, there is the whey, which is generated in large quantities, and has numerous technological properties when used in concentrated protein (WPC) or isolated protein (WPI). With this in mind, such biopolymers and oils from various branches of the food industry can be studied and developed to stabilize food emulsions in order to encapsulate and benefit from bioactive compounds. It is of utmost importance to ensure the stability of the emulsion, the method of complex coacervation being effective, since with the mixture and interaction of a particular protein with a specific polysaccharide, at a pH that have opposite charges, result in a complex, forming a matrix around the bioactive compound. Furthermore, it is of utmost importance to measure the rheological behavior and characteristics of emulsion systems, because the variation of any component can affect the physical properties and consequently the stability of emulsions, as well as the final product. Thus, this literature survey aims to deepen the knowledge about the raw materials and techniques mentioned, to evaluate the possible application of these biopolymers in stabilizing emulsions with lemon essential oils.
Lemon essential oil: its possible application in emulsions by complex coacervation method with wpc:pec
Keywords: bioactive compounds, emulsion stabilization, tahiti lemon, pectin, whey protein concentrate; Compostos bioativos; Estabilização de emulsões; Limão Tahiti; Pectina; Concentrado proteico de soro; Bioactive compounds; Emulsion stabilization; Tahiti lemon; Pectin; CIENCIAS AGRARIAS